WORKING CAPITAL MANAGEMENT IN INCREASING LIQUIDITY AND PROFITABILITY IN THE BUSINESSAREAOF TIRTA KOMODO MANGGARAI DRINKING WATER - Tanusi, Gabriel; Korsini Tauk, Andreas (Sean Institute, 2022)
Good management of working capital will determine the liquidity and profitability of the enterprise. This study aims to determine and analyze the working capital management of PDAM Tirta Komodo in 2018 - 2020 in determining liquidity and profitability. The type of data used is secondary data sourced from the balance sheet and profit and loss statements for 2018 - 2020. Data analysis techniques use the analysis of the ratio of working capital turnover, liquidity ratio, profitability ratio. The results of the analysis show that the turnover of working capital has decreased continuously, resulting in an impact on the company's financial ability to fulfill obligations to third parties, as seen from the acquisition of current ratios and quick ratios that have increased continuously. The decrease in working capital turnover also has a significantimpact on the company's profitability gains, which is seen from the attractive ratio of NPM, ROA and ROE. Efforts to increase liquidity and profitability can be done by: using cash optimally, increasing collection of receivables, reducing inventory collection in warehouses, controlling operational costs, increasing the number of current ICA andown capital.